Systematic Literature Review of Chemistry Learning to Improve Students’ Creative Thinking Skills - I Nyoman Suardana; I Wayan Redhana; Kompyang Selamet (Postgraduate, University of Mataram, 2024)
The purpose of this study is to discuss novel approaches to teaching chemistry that enhance students' creative thinking skills (CTSs), as well as the kinds of research that are conducted and the tools that are used to measure CTSs. . This research use the PRISMA paradigm in conjunction with a systematic literature review approach. This method was employed by searching for Google Scholar. The analysis results of eight relevant journals and proceeding articles show five articles discussing the implementation of chemistry learning strategies to improve students’ CTSs, with the distribution as follows: problem-based learning-scaffolding, STEAM-PjBL, case-based Learning, STMCpE textbooks based on chemo-entrepreneurship, and students’ worksheet with the mind mapping strategy which amounts to 20.00% each. The types of research used were experimental methods (37.50%), research and developmental methods (12.50%), survey research (12.50%), ex post facto research (12.50%), and qualitative research (descriptive approach) (25.00%). Instruments for measuring CTSs are in the form of a CTS test with indicators developed by Torrance (75.00%), non-test (interview and observation) (12.50%), and unclear instrument (12.50%).